Quantitative study on hepatic genotoxicity of neodymium and its molecular mechanisms based on Benchmark Dose method - Ning Wang (Frontiers in Pharmacology, 2024)
IntroductionNeodymium, a rare earth element, has been shown to induce genotoxicity in mice, but the molecular mechanisms behind this effect are not fully understood. This study aims to investigate the genotoxic effects of intragastric administration of neodymium nitrate (Nd(NO3)3) over 28 consecutive days and to elucidate the underlying molecular mechanisms.MethodsWe detected the content of neodymium in mouse liver tissue using ICP-MS and assessed the percentage of tail DNA in mouse hepatocytes using the alkaline comet assay to evaluate genotoxicity. Additionally, we evaluated genetic toxicological biomarkers (reactive oxygen species (ROS), 8-hydroxy-2′-deoxyguanosine (8-OHdG), and γ-H2AX) and the expression levels of genes related to the p53 pathway in the mouse liver.ResultsOur findings indicate a potential accumulation of (Nd(NO3)3) in the livers of mice, leading to DNA double-strand breaks in hepatocytes, as evidenced by comet and γ-H2AX assays. Nd(NO3)3 significantly increased the percentage of tail DNA in hepatocytes and upregulated the expression of molecules related to the p53 pathway, including ATM, Wip1, ATR, Chk2, MDM2, p53, p21, and NF-κB, at the transcriptional level. The treatment also effectively triggered the production of ROS, 8-OHdG, and γ-H2AX in liver tissue.DiscussionThese results suggest that (Nd(NO3)3) induces hepatic genotoxicity and injury in mice and modulates the expression of genes associated with DNA damage response, carcinogenesis, and inflammatory processes. The study provides insights into the molecular mechanisms by which neodymium nitrate exerts its genotoxic effects and underscores the importance of further investigating the potential health risks associated with neodymium exposure.